Uji Aktivitas Tabir Surya Ekstrak Etanol Kulit Markisa Ungu secara In Vitro dengan Spektrofotometri Uv-Vis - Agtri, Nisa Aulia; Ariastuti, Reni; Qonitah, Fadilah (Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
Excessive exposure to Ultraviolet (UV) radiation can cause skin damage, including erythema, premature ageing, and skin cancer. Sunscreen is commonly used to protect the skin from UV radiation. The peel of purple passion fruit (Passiflora edulis) contains phenolic and flavonoid compounds that may provide UV-absorbing activity. This study aimed to evaluate the sunscreen activity of the ethanol extract of purple passion fruit peel in vitro based on the Sun Protection Factor (SPF), Erythema Transmission Percentage (%Te), and Pigmentation Transmission Percentage (%Tp). The extract was obtained by maceration with 96% ethanol. Qualitative identification of phenolic compounds was performed using a FeCl3 reagent, while flavonoids were detected using concentrated HCl and magnesium powder. Sunscreen activity was evaluated using UV-Vis spectrophotometry at concentrations of 400, 600, 800, 1,000, and 1,200 ppm. The results showed that the extract contained phenolic and flavonoid compounds. At the highest concentration (1,200 ppm), the SPF value was 20.086±1.696 (ultra-protection), %Te was 0.697±0.149, and %Tp was 4.413±0.594, all of which were categorised as sunscreen. One-way ANOVA analysis indicated significant differences among concentration variations (p<0.05). In conclusion, the ethanol extract of purple passion fruit peel has potential as a natural active ingredient for sunscreen.